Sports Integration to Develop Understanding related to Physics Concept: A Cross-Curricular Pedagogical Approach - Sharma, Anjali; Sharma, Ranjana; Maurya, Vijay (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Using indigenous games as learning tools to understand physics concepts is a good idea that can play a vital role in developing an activity-based physics curriculum. In this study, GulliDanda was used to explain the trajectories of projectiles. This research aims to reveal the effectiveness of this cross-curricular pedagogical approach in cognitive(achievement), affective and psychomotor domain. The quasi-experimental single group post-test design was adopted to carry out the research. A sample of thirty students belonging to the science discipline from class 11th has been selected for the study. The effectiveness of the indigenous knowledge-based physics path of the projectile object (Gulli) was analyzed. During the playing game, it is demonstrated that the trajectory traced by Gulli is parabolic in nature. It is concluded from the study that Students can engage more readily with indigenous games that help them develop prior knowledge, logical reasoning, concentration, and build their inquiry-based scientific temper epistemologically. This cross curricular pedagogical approach provides experiential learning to learners in realistic conditions.